Innovative Solutions in the Tourism and Hospitality Industry to Ensure Sustainable Development in a New Normality - Morozov, Mikhail; Morozova, Natalia (Anais Brasileiros de Estudos Turísticos, 2022)
The article examines topical issues of the functioning of the tourism and hospitality industry in the context of the new normalcy caused by the COVID-19 pandemic. The pandemic has led to a sharp decline in tourist flows and the need for innovative solutions to restore and further develop the tourism and hospitality industry. In the context of the new normality, the classical interpretation of the concept of the quality of tourist and hotel services and sustainable development of tourism is changing. When assessing the quality of services in tourism, the assessment of their epidemiological safety began to occupy a key place. The sustainable development of tourism is significantly influenced by global digitalization and the formation of a new category of digital tourists. The article analyzes innovative solutions to ensure travel safety and sustainable development of the tourism industry in the context of the new normalcy. It is shown that in the context of a pandemic, there was an acceleration of the processes of introducing innovations, including digitalization in the field of tourism. It is proposed to expand the understanding of sustainable tourism development by including digital information support as a prerequisite for meeting the requirements of digital tourists.